Inclusion of oral health teams in primary health care promotes early diagnosis of oral and oropharyngeal cancers: a nationwide study - Deborah Gomes de Miranda Vargas; Livia Fernandes Probst; Amanda Ramos da Cunha; Elaine Pereira da Silva Tagliaferro; Edílson José Zafalon; Paulo Zárate-Pereira; Alessandro Diogo De-Carli (BMC, 2021)
Abstract Background Oral and oropharyngeal cancers are considered important public health problems worldwide. This study aims to analyze the association between late diagnosis of oral and oropharyngeal cancers in Brazil and the contextual indicators of socioeconomic variables and coverage of Primary Health Care (PHC), and to assess the temporal trend of late diagnosis. Methods In this cross-sectional observational study, secondary data were evaluated with a time series analysis. All Brazilian cities that reported at least one case of oral and oropharyngeal cancers each year in the period between 2000 and 2013 were included; and the staging was analyzed by calculating the ratio risk for late diagnosis for each municipality. The association between staging and socioeconomic variables and offer of PHC was calculated using multiple linear regression. The time trend of the risk ratio for late-stage diagnosis was calculated using the Prais-Winsten method. Results One hundred and sixty Brazilian municipalities had at least one annual case of oral and oropharyngeal cancers notified to the INCA hospital system between 2000 and 2013. The adjusted model showed that the higher the Gini value (greater social inequality) and the lower the HDI value (less human development) was, the higher was the number of tumors diagnosed at a late stage, considering the size of the tumor. A greater risk for late diagnosis was identified, as early as at the stage of lymph node involvement, when there was a higher level of social inequality and lower level of coverage by Oral Health Teams (OHT) in PHC. The greater the social inequality, the greater was the risk of late diagnosis, as early as in the stage of metastasis. Conclusions We concluded that, during the evaluated period, there was an increase in the number of cases diagnosed at the most advanced stage. Furthermore, there was association between higher levels of social inequality and an increase in the proportion of late diagnosis of oral and oropharyngeal cancers. In addition, the inclusion of Oral Health Teams in Primary Health Care promoted the early diagnosis of these types of cancers.